Pengaruh Penggunaan Media Nyata Berupa Peta Timbul pada Materi Peta Kelas X terhadap Hasil Belajar Siswa di SMA 1 Pertiwi Kota Padang - Ediansyah, Fadila Aprilia; Chandra, Deded (Lembaga Yasin AlSys, 2025)
The objectives of this study are 1) To determine the influence of the use of real media in the form of embossed maps in class x map material on the learning outcomes of students at SMA 1 Pertiwi Padang 2) To find out the learning outcomes of students who use embossed map media and those who do not use embossed map media. This study uses a quantitative method with an experimental type of research. The pretest was carried out in two groups to find out the basic abilities of each control and experiment class. The population in this study is all students of class X of SMA 1 Pertiwi Kota Padang which totals 264 students with 2 class samples with purposive sampling techniques. The variables in this study are divided into 2 namely independent variables and bound variables. The data sources in this study are primary and secondary data. The collection techniques in this study are test, questionnaire and documentation techniques. The research procedure in this study was carried out in 2 classes, namely the experimental and control classes. The test of this research instrument is a test of validity, reliability, and differentiation. The data analysis tests in this study were the normality test, homogeneity, hypothesis test (T), and N-Gain test. The results of this study show that 1) The use of real media in the form of embossed maps on map material has an effect on student learning outcomes at SMA 1 Pertiwi Padang which is seen through the results of hypothesis testing (T) which is also supported by the improvement of student learning outcomes after using embossed map media in the experimental class and then an N-Gain test with a score of 82.50% for the embossed map media group and 60.00% for the conventional media group (lecture). 2) To find out the learning outcomes of students who use pop-up map media and those who do not use pop-up map media have been fulfilled with the scores of students who use pop-up map media higher than students who do not use pop-up map media as seen from the N-Gain Test. One of the advantages of using Embossed Map Media is the high level of interactivity through the practice of making embossed maps. Pop-up Map Media provides a non-boring learning experience for students.